2004
DOI: 10.1136/vr.154.8.223
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the presence of hepatitis E virus in pigs in the United Kingdom

Abstract: Samples of serum, tissue and faeces from two pig herds in England were examined for hepatitis E virus by reverse-transcriptase PCR (RT-PCR), and a virus strain from each herd was partially sequenced. Eleven of 42 faecal samples and 16 of 21 tissue samples from two pigs were positive for the virus by RT-PCR. Analysis of two unique but closely related nucleotide sequences obtained from the two herds showed that the viruses clustered in genotype III (6) with a human strain of the virus from an autochthonously acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
84
2

Year Published

2006
2006
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 34 publications
(49 reference statements)
3
84
2
Order By: Relevance
“…Infection in pigs can be symptomatic [59][60][61] but most often infections remain clinically undetected [47,[62][63][64][65]. Close relatedness has been found between HEV gt3 nucleotide sequences from pigs and wild boar and those from human cases [6,32,41,51,60,61,63,64,[66][67][68][69][70][71].…”
Section: Potential For Zoonotic Transmission By Direct Animal Contactmentioning
confidence: 99%
“…Infection in pigs can be symptomatic [59][60][61] but most often infections remain clinically undetected [47,[62][63][64][65]. Close relatedness has been found between HEV gt3 nucleotide sequences from pigs and wild boar and those from human cases [6,32,41,51,60,61,63,64,[66][67][68][69][70][71].…”
Section: Potential For Zoonotic Transmission By Direct Animal Contactmentioning
confidence: 99%
“…A study in which sera from 336 Spanish patients diagnosed for idiopathic acute hepatitis was reevaluated 14 found seroprevalence of 8.9% using anti-HEV IgM. Other studies carried out in several European countries such as Austria, 21 England, 2 France, 9 and Italy 23 have found autochthonous cases with a high percentage of nucleotide similarity to porcine strains from the same geographic area. In summary, this work could serve to highlight the production stages in which pigs are in most danger of infecting other pigs.…”
mentioning
confidence: 99%
“…In the UK, 26.19% of 12-to 15-week-old pigs were found to be shedding HEV in feces on 2 farms studied. 2 In New Zealand, 37.8% of 7-to 17-week-old pigs from 2 farms (45 pigs) were found to be shedding HEV in feces. 5 In the USA 25 (26.3%) 2-to 4-month-old pigs out of 95 were reported to be shedding the virus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pigs are supposed to be infected with HEV via the fecal-oral route continuously, since pigs habitually eat feces naturally. Several epidemiological studies reported HEV shedding in up to 17-week-old pigs [23,[30][31][32]. An opportunity to come in contact with contaminated feces increases the intake of virus by pigs.…”
Section: Discussionmentioning
confidence: 99%